Effect of β-naphthoflavone on hepatic cytochrome P4501A activity in the scribbled rabbitfish (Siganus spinus) from tropical Indo-Pacific coral reefs - Emborski, Carmen (Ecotoxicology (London, England), 2012)
Several classes of carcinogenic environmental organic pollutants, including polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and dioxins, negatively affect aquatic ecosystems worldwide. Pollutant detection is often difficult and expensive, especially when dealing with complex mixtures and matrices. Biological markers are informative tools to identify living sources that may harbor toxic compounds and areas unsuitable for recreation. Currently, no species have established biomarkers for organopollutant monitoring in Indo-Pacific coral reefs. This study evaluated the time- and dose-dependent induction of the cytochrome P4501A (CYP1A) system in the scribbled rabbitfish, Siganus spinus (Siganidae), as a biomarker for organic pollutant exposures in these environments. Results indicate that S. spinus hepatic CYP1A enzymatic activity and protein level respond dose-, and time-dependently following a single intraperitoneal injection of the classic aryl hydrocarbon receptor agonist, β-naphthoflavone. S. spinus hepatic CYP1A protein and enzymatic activity rose as function of dose during the first two days and slowly returned to levels close to normal after 16 days, as measured using the 7-ethoxyresorufin-O-deethylase and the non-competitive enzyme-linked immunosorbent assays, respectively. These findings support use of the inducible CYP1A system of S. spinus as a biomarker for reef fish exposure to coastal marine pollution. Baseline CYP1A expression levels among Guam's wild S. spinus populations were also measured and compared